Effect of Mn doping and charge transfer on LaTi1−xMnxO3. (8th February 2023) - Cao, Guixin; Weng, Yakui; Yao, Xinyu; Ward, T Zac; Gai, Zheng; Mandrus, David; Dong, Shuai
Abstract: We report the magnetic and electronic transport properties of Mn-doped LaTi1− x Mn x O3 ( x = 0, 0.1, 0.3, 0.5) as a function of temperature and an applied magnetic field. It was found that the Mn-doped samples show a magnetic transition which is not present in the parent LaTiO3 . The Mn-doped samples showed fluctuations in magnetization at low fields below their Néel transition temperature indicating electronic phase separation in the material. Increased Mn content in the sample strengthens the ferromagnetic-like moment while maintaining G-type antiferromagnetic phase by charge transfer from Mn to Ti and influencing orbital ordering of the Ti 3+ t2g orbitals. The results are discussed in parallel with transport and bulk magnetization measurements detailing the electronic behavior. An additional context for the mechanism is supported by first-principles density-function theory calculations.